IDENTIFIKASI JENIS TANAH PADA LAHAN PEMUKIMAN BERDASARKAN INTEGRASI PENGUKURAN GEOLISTRIK 3D DAN UJI INDEKS PROPERTIES TANAH DI PERUMAHAN ISTANA TIDAR REGENCY-JEMBER - Supriyadi Supriyadi; N Priyantari; D.P Sulistyani; W.A Mayasari (Lambung Mangkurat University Press, 2016)
Geoelectrical 3D resitivity measurement and soil’s index properties test has been conducted to determine soil type on settlement area Istana Tidar Regency, Jember. Resistivity measurement and soil sampling conducted at unoccupied area that have latitude (08°10’10,1” -08°10’11,9”) S and longitude (113°43’40,0”- 113°43’41,1”) E. Resistivity image of subsurface structure show that this settlement area was dominated by silty clay and sandysilt.To obtain more detailed information about the type of soil and its physical – mechanical properties, laboratory test done using soil’s index properties test. The result of soil’s index properties test show that this settlement area was dominated by silty clay have fine sand gradation and moderate plasticity.